EFEKTIVITAS TERHADAP PENGUTIPAN PAJAK PARKIR DALAM HUBUNGANNYA DENGAN PENINGKATAN PENDAPATAN DAERAH DI KOTA MEDAN MENURUT PERDA KOTA MEDAN NO. 10 TAHUN 2011 - Fitri Handryani; Muhammad Abduh; Faisal Akbar Nasution; Pendastaren Tarigan (USU LAW JOURNAL, 2014)
ABSTRACT In collecting the parking tax in Medan particularly always contribute to local administration income of Medan, and in field it shall depend on how effectiveness to collect it. This study is aimed to deal with the matters regarding the methods, effectiveness and the barriers found in collecting the parking tax and how its contribution to improve more city income of Medan administration. The result of this research that through the planning stages (data collection), execution (deposit) and supervision, which also embraced self assessment system. Furthermore, local income tax is less effective than the parking sector because the number of parking tax-acquired very rarely reach the target. Bottleneck that occurs in sources of income is the presence of a target area that has been designated parking tax is not comparable to the true potential, the presence of an imbalance between the actual potential possessed by the parking tax revenue and local revenue realization that has been done, so the government is making efforts to regulations areas in which sanctions with the aim of supervision.   Keywords : Parking tax, City Administration income.